Abundance changes of neophytes and native species indicate a thermophilisation and eutrophisation of the Swiss flora during the 20th century. (February 2022) - Scherrer, Daniel; Bürgi, Matthias; Gessler, Arthur; Kessler, Michael; Nobis, Michael P.; Wohlgemuth, Thomas
Highlights: Floristic shifts during the 20 th century indicate both a thermophilisation and eutrophisation. Strong increase in neophytes profiting from both land-use changes and climate warming. Native species of colder and nutrient poor habitats are decreasing and disappearing. Abstract: During the 20 th century human activities drastically altered the natural environment at global and local scales by habitat destruction, urbanisation, intensive agriculture, and climate warming. This anthropogenic pressure has modified species distributions and abundances, and led to the increased spread of neophytes. However, the determination of the magnitude, direction, and drivers of changes remains challenging as comparable historic data is often lacking. Here, we analysed the floristic shifts during the 20 th century based on a historic (1900–1930) and current (2000–2017) floristic survey of the canton of Zurich (Switzerland; 1729 km 2 ) in combination with Landolt ecological indicator values (EIVs) for vascular plants. We used two complementary approaches to quantify the floristic shifts using EIVs for temperature, moisture, continentality, nutrients, soil pH and available light. 1) Regarding 244 map tiles with each a 3 × 3 km 2 area, we compared the average EIVs for neophytes (i.e., novel species arriving of expanding in the study area) and native species (i.e., species present in Switzerland for centuries). 2) Based on standardized species abundances in the historic and the current flora, we analysed the directed changes by comparing the species' EIVs of different frequency classes for both the historic and current floristic surveys. Our results showed, that neophyte species arriving or spreading in the study area indicate both a thermophilisation and an eutrophisation. The observed shift in average EIVs for temperature corresponded to about 2 °C, which is in line with the calculated difference in niche centroids for neophytes and native species based on their global distribution (1.78 °C). The indicated thermophilisation and eutrophisation relate to the decrease in abundances of cold-adapted species and species of nutrient poor environments as well as the increase of warm-adapted and nitrophilous/ruderal species. Directed changes in the flora of the study area are likely to be driven by both climatic changes and land-use changes. Increases in trade activity, anthropogenic habitat disturbances and rising temperatures facilitate the establishment and spread of neophytes from warmer and drier regions. In parallel, wetland area and wetland species strongly decreased as well as species thriving on nutrient-poor sites due to intensified agriculture and nitrogen deposition.